A bio-based anti-drip PET fiber and preparation method thereof

By using calcium alginate fibers and modified polycaprolactone, bio-based anti-droplet PET fibers prepared by soaking in aqueous zinc nitrate solution, the problem of poor melting and antibacterial effects during combustion of PET fibers is solved, and significant results are achieved Improved flame retardant and antibacterial properties.

CN118621469BActive Publication Date: 2025-01-14QINGDAO QINDAO NON WOVEN PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410743597.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-01-14
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

At this stage, PET fibers are prone to melt droplets when burning, and the antibacterial effect is poor, resulting in a high risk of spontaneous combustion of electric blankets at high temperatures and affecting safety.

Method used

Use calcium alginate fibers and modified polycaprolactone as raw materials to prepare modified fibers through glutaraldehyde cross-linking and aldol condensation reaction, and soak them in zinc nitrate aqueous solution to increase antibacterial and flame retardant effects to form a loaded metal zinc The flame retardant properties are enhanced by phosphorus, nitrogen and boron elements.

Benefits of technology

It significantly improves the antibacterial and flame retardant properties of PET fibers, prevents the generation of melt droplets, reduces the oxygen concentration, forms a carbonized layer to isolate heat, enhances the density of the carbonized layer, captures the hydrogen free radicals generated by combustion, and improves the flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005111636910000131
    Figure GDA0005111636910000131
Patent Text Reader

Abstract

The invention discloses a bio-based anti-melting droplet PET fiber and a preparation method thereof, and relates to the technical field of anti-melting droplet fiber preparation. The PET fiber comprises the following raw materials in parts by weight: 80-100 parts of modified PET and 10-20 parts of modified fiber; the surface of the PET fiber is loaded with metal zinc, which is matched with the modified polylactic acid in the modified fiber to increase the antibacterial effect; the surface of the modified polylactic acid is weakly acidic and can inhibit the growth of microorganisms; the modified PET contains multiple elements such as phosphorus, nitrogen, boron and silicon; phosphorus can generate phosphoric anhydride and phosphide; phosphoric anhydride can dehydrate and carbonize the PET, and form a carbonized layer on the surface to isolate external heat; nitrogen element can generate nitrogen and amino groups to dilute the oxygen content; boron, silicon and metal zinc on the surface can enhance the compactness of the carbonized layer, thereby preventing the generation of molten droplets; and the phosphide can capture hydrogen free radicals generated by the combustion of ABS, thereby improving the flame retardant effect of the PET fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of anti-drip fibers, and in particular to a bio-based anti-drip PET fiber and a preparation method thereof. Background Art

[0002] Polyester fiber, referred to as PET fiber, belongs to polymer compounds. It is the largest variety of synthetic fiber at present. Synthetic fiber is a chemical fiber made by spinning and post-processing a linear polymer with suitable molecular weight and solubility (or fusibility). Synthetic fiber is also a petroleum-based fiber. It faces problems such as excessive fluctuations in crude oil prices, serious lack of domestic raw material production capacity, relatively weak R&D capabilities, risks brought by changes in industry policies, and the impact of opening up to the outside world, and it is unsustainable. This fiber is widely used in various fields, including the electric blanket industry. Electric blankets have become a tool for heating in many families. At present, electric blankets use a single fiber layer as a blanket material. Such electric blankets often have the risk of spontaneous combustion when the temperature is too high. Many users are scalded in this way. In severe cases, fires will occur, causing damage to people's lives and property, and seriously affecting people's normal study and life. Traditional electric blanket materials have no flame retardant properties, and have great safety hazards. They cannot prevent combustion well and cannot fundamentally solve the problem of overheating and combustion of electric blankets. Summary of the invention

[0003] The purpose of the present invention is to provide a bio-based anti-drip PET fiber and a preparation method thereof, which solves the problem that PET fiber is prone to dripping when burned and has poor antibacterial effect at the current stage.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a bio-based anti-drip PET fiber specifically comprises the following steps:

[0006] Calcium alginate fiber, modified polycaprolactone, glutaraldehyde and ethyl acetate are mixed and stirred for 3-4 hours at a speed of 60-80r / min and a temperature of 40-50°C to obtain modified fiber. The following raw materials are weighed in parts by weight: 80-100 parts of modified PET and 10-20 parts of modified fiber. The raw materials are added into a twin-screw extruder and melt-extruded under the conditions that the temperatures of four zones are 230°C, 265°C, 265°C, and 265°C, respectively, and the pipeline temperature is 260°C. Then, the raw materials are melt-spun under the conditions that the number of spinneret holes is 36, the side blowing power is 10Hz, the oil pump power is 20Hz, the component pressure is 6-9MPa, the spinning temperature is 270-280°C, and the winding speed is 800m / min to obtain pretreated PET fiber. The pretreated PET fiber is immersed in an aqueous solution of zinc nitrate for 1-2h and dried to obtain bio-based anti-drip PET fiber.

[0007] The mass ratio of the calcium alginate fiber, modified polycaprolactone and glutaraldehyde is 1:10:0.05, and the mass fraction of the zinc nitrate aqueous solution is 10%.

[0008] Further, the modified polycaprolactone is prepared by the following steps:

[0009] Step A1: 2,2-dihydroxymethylpropionic acid, acetyl chloride, triethylamine and DMF are mixed, and the reaction is carried out for 10-15 hours at a speed of 120-150 r / min and a temperature of 0° C. to obtain intermediate 1; intermediate 1, thionyl chloride and DMF are mixed, and the reaction is carried out for 10-12 hours at a speed of 150-200 r / min and a temperature of 80-90° C. to obtain intermediate 2;

[0010] Step A2: The intermediate 2, 4-aminoimidazole, triethylamine and DMF are mixed evenly, and the mixture is reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of -5-0°C to obtain the intermediate 3. The intermediate 3 and deionized water are mixed evenly, and the mixture is stirred at a speed of 120-150 r / min and a temperature of 20-25°C, and sodium hydroxide is added to the mixture until the pH value reaches 9-10, and the mixture is reacted for 2-3 hours to obtain the modified monomer.

[0011] Step A3: uniformly mix the modified monomer, caprolactone, stannous octoate and toluene, introduce nitrogen protection, and react for 20-25 hours at a speed of 60-80 r / min and a temperature of 110-120° C. to obtain modified polycaprolactone.

[0012] Furthermore, the molar ratio of 2,2-dihydroxymethylpropionic acid, acetyl chloride and triethylamine in step A1 is 1:2:2.1, and the molar ratio of intermediate 1 and thionyl chloride is 1:1.2.

[0013] Furthermore, the molar ratio of the intermediate 2, 4-aminoimidazole and triethylamine described in step A2 is 1:1:1.2, and the amount ratio of the intermediate 3 and deionized water is 1g:40mL.

[0014] Furthermore, the usage ratio of the modified monomer, caprolactone and stannous octoate described in step A3 is 60 mmol:450 mmol:2.5 mL.

[0015] Further, the modified PET is prepared by the following steps:

[0016] Step B1: Tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 90-95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, propylene oxide and DMF are mixed uniformly, and the reaction is carried out for 6-8 hours at a speed of 150-200 r / min, a temperature of 40-50° C. and a pH value of 10-11 to obtain a pretreated polysiloxane;

[0017] Step B2: The pretreated polysiloxane, DOPO and DMF are mixed evenly, and reacted at a speed of 120-150 r / min and a temperature of 100-110° C. for 5-7 hours to obtain a modified polysiloxane; 3,4-dihydroxybenzoic acid, 4-formylphenylboric acid, sodium carbonate and chloroform are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 60-80 r / min and a temperature of 60-65° C. for 10-15 hours to obtain a modifier;

[0018] Step B3: The modifier, modified polysiloxane, p-toluenesulfonic acid monohydrate and isopropanol are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 15-18 hours at a speed of 150-200r / min and a temperature of 20-25°C to obtain a flame retardant monomer. The flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite, ethylene glycol and antimony trioxide are mixed evenly, and the reaction is carried out for 3-5 hours at a temperature of 230-240°C and a pressure of 0.3-0.5MPa. The temperature is raised to 280-285°C, and the reaction is carried out for 20-30 minutes at a pressure of 50-80Pa to obtain a modified PET.

[0019] Furthermore, the molar ratio of tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 1.2:1:1.5, and the molar ratio of diamine-terminated polysiloxane and propylene oxide is 1:4.

[0020] Furthermore, the molar ratio of the double bonds on the pretreated polysiloxane in step B2 to DOPO is 1:1, the molar ratio of 3,4-dihydroxybenzoic acid to 4-formylphenylboronic acid is 1:1.3, and the amount of sodium carbonate used is 5% of the mass of 3,4-dihydroxybenzoic acid.

[0021] Furthermore, the molar ratio of the modifier and the modified polysiloxane described in step B3 is 2:1, the amount of p-toluenesulfonic acid monohydrate is 2% of the total mass of the modifier and the modified polysiloxane, the molar ratio of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol is 1:5:1:7.8, and the amount of antimony trioxide is 3% of the total mass of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol.

[0022] Beneficial effects of the present invention: A bio-based anti-melting PET fiber prepared by the present invention comprises the following raw materials: modified PET and modified fiber, the modified fiber is made of calcium alginate fiber and modified polycaprolactone as raw materials, glutaraldehyde is used as a cross-linking agent, and an aldol condensation reaction is carried out to obtain the modified fiber, the modified polycaprolactone is made of 2,2-dihydroxymethylpropionic acid and acetyl chloride as raw materials for hydroxyl protection to obtain intermediate 1, the intermediate 1 is reacted with thionyl chloride to convert the carboxyl group on the intermediate 1 into an acyl chloride to obtain intermediate 2, the intermediate 2 is reacted with 4-aminoimidazole to react the acyl chloride on the intermediate 2 with the amino group on the 4-aminoimidazole to obtain intermediate 3, the intermediate 3 is deprotected under alkaline conditions to obtain a modified monomer, the modified monomer and caprolactone are esterified and copolymerized to obtain the modified polycaprolactone.

[0023] The modified PET is prepared by ring-opening polymerization of tetramethyltetravinylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane as raw materials to obtain diamine-terminated polysiloxane, and the diamine-terminated polysiloxane is reacted with propylene oxide to make the amino groups on the diamine-terminated polysiloxane react with the epoxy groups on the propylene oxide to form hydroxyl groups to obtain pretreated polysiloxane, and the pretreated silane is reacted with DOPO to make the double bonds on the pretreated polysiloxane The invention relates to a novel polysiloxane comprising a flame retardant and a terephthalic acid. The flame retardant is prepared by reacting the PH bond on DOPO to obtain a modified polysiloxane, reacting 3,4-dihydroxybenzoic acid with 4-formylphenylboronic acid so that the bisphenol structure on the 3,4-dihydroxybenzoic acid reacts with the boronic acid group on the 4-formylphenylboronic acid to obtain a modifier, and the modifier and the modified polysilane are subjected to an acetal reaction to obtain a flame retardant monomer, and the flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite and ethylene glycol are esterified and polymerized to obtain a modified PET.

[0024] When the pretreated PET fiber is immersed in a zinc nitrate aqueous solution, the imidazole groups on the surface of the PET fiber can complex with zinc ions, so that the surface is loaded with metallic zinc, thereby increasing the antibacterial and flame retardant effects of the PET fiber. The surface of the modified polycaprolactone is weakly acidic, which will inhibit the growth of microorganisms and achieve antibacterial effects. The modified PET contains multiple elements such as phosphorus, nitrogen, boron and silicon. Phosphorus can generate phosphoric anhydride and phosphide. Phosphoric anhydride can dehydrate and carbonize PET, forming a carbonized layer on the surface to isolate external heat. Nitrogen can generate nitrogen and amino groups to dilute the oxygen content. Boron, silicon and metallic zinc on the surface can enhance the density of the carbonized layer, thereby preventing the generation of molten droplets. At the same time, phosphide can capture hydrogen free radicals generated by ABS combustion, thereby improving the flame retardant effect of the PET fiber. When calcium alginate fiber burns, an alkaline environment will be formed. The hydroxyl groups contained in the fiber macromolecules are prone to decarboxylation in an alkaline environment to form carbon dioxide gas, which will reduce the oxygen concentration around the fiber. Secondly, calcium oxide and calcium carbonate generated during combustion cover the fiber surface to isolate the air and further improve the flame retardant effect. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A method for preparing a bio-based anti-drip PET fiber specifically comprises the following steps:

[0028] Calcium alginate fiber, modified polycaprolactone, glutaraldehyde and ethyl acetate are mixed and stirred for 3 hours at a speed of 60 r / min and a temperature of 40°C to obtain modified fibers. The following raw materials are weighed in parts by weight: 80 parts of modified PET and 10 parts of modified fibers. The raw materials are added into a twin-screw extruder and melt-extruded under the conditions that the temperatures in four zones are 230°C, 265°C, 265°C, and 265°C, respectively, and the pipeline temperature is 260°C. Then, the raw materials are melt-spun under the conditions that the number of spinneret holes is 36, the side blowing power is 10Hz, the oil pump power is 20Hz, the component pressure is 6MPa, the spinning temperature is 270°C, and the winding speed is 800m / min to obtain pretreated PET fibers. The pretreated PET fibers are immersed in an aqueous solution of zinc nitrate for 1-2 hours and dried to obtain bio-based anti-drip PET fibers.

[0029] The mass ratio of the calcium alginate fiber, modified polycaprolactone and glutaraldehyde is 1:10:0.05, and the mass fraction of the zinc nitrate aqueous solution is 10%.

[0030] The modified polycaprolactone is prepared by the following steps:

[0031] Step A1: 2,2-dihydroxymethylpropionic acid, acetyl chloride, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 120 r / min and a temperature of 0° C. for 10 h to obtain intermediate 1; intermediate 1, thionyl chloride and DMF were mixed, and the mixture was reacted at a speed of 150 r / min and a temperature of 80° C. for 10 h to obtain intermediate 2;

[0032] Step A2: The intermediate 2, 4-aminoimidazole, triethylamine and DMF were mixed evenly, and the mixture was reacted for 3 hours at a speed of 150 r / min and a temperature of -5°C to obtain the intermediate 3. The intermediate 3 and deionized water were mixed evenly, and the mixture was stirred at a speed of 120 r / min and a temperature of 20°C, and sodium hydroxide was added to a pH value of 9, and the mixture was reacted for 2 hours to obtain the modified monomer.

[0033] Step A3: The modified monomer, caprolactone, stannous octoate and toluene are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out at a speed of 60 r / min and a temperature of 110° C. for 20 hours to obtain modified polycaprolactone.

[0034] The molar ratio of 2,2-dihydroxymethylpropionic acid, acetyl chloride and triethylamine in step A1 is 1:2:2.1, and the molar ratio of intermediate 1 and thionyl chloride is 1:1.2.

[0035] The molar ratio of intermediate 2, 4-aminoimidazole and triethylamine described in step A2 is 1:1:1.2, and the amount ratio of intermediate 3 and deionized water is 1g:40mL.

[0036] The usage ratio of the modified monomer, caprolactone and stannous octoate described in step A3 is 60mmol:450mmol:2.5mL.

[0037] The modified PET is prepared by the following steps:

[0038] Step B1: Tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 90° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, propylene oxide and DMF are mixed uniformly, and the reaction is carried out for 6 hours at a speed of 150 r / min, a temperature of 40° C. and a pH value of 10 to obtain a pretreated polysiloxane;

[0039] Step B2: The pretreated polysiloxane, DOPO and DMF were mixed evenly, and reacted at a speed of 120 r / min and a temperature of 100° C. for 5 h to obtain a modified polysiloxane; 3,4-dihydroxybenzoic acid, 4-formylphenylboric acid, sodium carbonate and chloroform were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 60 r / min and a temperature of 60° C. for 10 h to obtain a modifier;

[0040] Step B3: The modifier, modified polysiloxane, p-toluenesulfonic acid monohydrate and isopropanol are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 15 hours at a speed of 150r / min and a temperature of 20°C to obtain a flame retardant monomer. The flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite, ethylene glycol and antimony trioxide are mixed evenly, and the reaction is carried out for 3 hours at a temperature of 230°C and a pressure of 0.3MPa. The temperature is raised to 280°C and the reaction is carried out for 20 minutes at a pressure of 50Pa to obtain a modified PET.

[0041] The molar ratio of tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 1.2:1:1.5, and the molar ratio of diamine-terminated polysiloxane and propylene oxide is 1:4.

[0042] The molar ratio of the double bonds on the pretreated polysiloxane in step B2 to DOPO is 1:1, the molar ratio of 3,4-dihydroxybenzoic acid to 4-formylphenylboronic acid is 1:1.3, and the amount of sodium carbonate used is 5% of the mass of 3,4-dihydroxybenzoic acid.

[0043] The molar ratio of the modifier and the modified polysiloxane described in step B3 is 2:1, the amount of p-toluenesulfonic acid monohydrate is 2% of the total mass of the modifier and the modified polysiloxane, the molar ratio of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol is 1:5:1:7.8, and the amount of antimony trioxide is 3% of the total mass of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol.

[0044] Example 2

[0045] A method for preparing a bio-based anti-drip PET fiber specifically comprises the following steps:

[0046] Calcium alginate fiber, modified polycaprolactone, glutaraldehyde and ethyl acetate are mixed and stirred for 3.5 hours at a speed of 60 r / min and a temperature of 45°C to obtain modified fibers. The following raw materials are weighed in parts by weight: 90 parts of modified PET and 15 parts of modified fibers. The raw materials are added into a twin-screw extruder and melt-extruded under the conditions that the temperatures in four zones are 230°C, 265°C, 265°C, and 265°C, respectively, and the pipeline temperature is 260°C. Then, pretreated PET fibers are obtained under the conditions that the number of spinneret holes is 36, the side blowing power is 10Hz, the oil pump power is 20Hz, the component pressure is 8MPa, the spinning temperature is 275°C, and the winding speed is 800m / min. The pretreated PET fibers are immersed in an aqueous solution of zinc nitrate for 1-2 hours and dried to obtain bio-based anti-drip PET fibers.

[0047] The mass ratio of the calcium alginate fiber, modified polycaprolactone and glutaraldehyde is 1:10:0.05, and the mass fraction of the zinc nitrate aqueous solution is 10%.

[0048] The modified polycaprolactone is prepared by the following steps:

[0049] Step A1: 2,2-dihydroxymethylpropionic acid, acetyl chloride, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 120 r / min and a temperature of 0° C. for 13 h to obtain intermediate 1; intermediate 1, thionyl chloride and DMF were mixed, and the mixture was reacted at a speed of 150 r / min and a temperature of 85° C. for 11 h to obtain intermediate 2;

[0050] Step A2: The intermediate 2, 4-aminoimidazole, triethylamine and DMF were mixed evenly, and the mixture was reacted for 4 hours at a speed of 150 r / min and a temperature of -3°C to obtain the intermediate 3. The intermediate 3 and deionized water were mixed evenly, and the mixture was stirred at a speed of 120 r / min and a temperature of 23°C, and sodium hydroxide was added to a pH value of 9, and the mixture was reacted for 2.5 hours to obtain the modified monomer.

[0051] Step A3: The modified monomer, caprolactone, stannous octoate and toluene are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out at a speed of 60 r / min and a temperature of 115° C. for 23 hours to obtain modified polycaprolactone.

[0052] The molar ratio of 2,2-dihydroxymethylpropionic acid, acetyl chloride and triethylamine in step A1 is 1:2:2.1, and the molar ratio of intermediate 1 and thionyl chloride is 1:1.2.

[0053] The molar ratio of intermediate 2, 4-aminoimidazole and triethylamine described in step A2 is 1:1:1.2, and the amount ratio of intermediate 3 and deionized water is 1g:40mL.

[0054] The usage ratio of the modified monomer, caprolactone and stannous octoate described in step A3 is 60mmol:450mmol:2.5mL.

[0055] The modified PET is prepared by the following steps:

[0056] Step B1: Tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the mixture is reacted for 4 hours at a speed of 120 r / min and a temperature of 93° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, propylene oxide and DMF are mixed uniformly, and the mixture is reacted for 7 hours at a speed of 150 r / min, a temperature of 45° C. and a pH value of 11 to obtain a pretreated polysiloxane;

[0057] Step B2: The pretreated polysiloxane, DOPO and DMF were mixed evenly, and reacted at a speed of 120 r / min and a temperature of 105° C. for 6 hours to obtain a modified polysiloxane; 3,4-dihydroxybenzoic acid, 4-formylphenylboric acid, sodium carbonate and chloroform were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 60 r / min and a temperature of 63° C. for 13 hours to obtain a modifier;

[0058] Step B3: The modifier, modified polysiloxane, p-toluenesulfonic acid monohydrate and isopropanol are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 16 hours at a speed of 150r / min and a temperature of 23°C to obtain a flame retardant monomer. The flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite, ethylene glycol and antimony trioxide are mixed evenly, and the reaction is carried out for 3-5 hours at a temperature of 235°C and a pressure of 0.4MPa. The temperature is raised to 280°C and the reaction is carried out for 25 minutes at a pressure of 65Pa to obtain a modified PET.

[0059] The molar ratio of tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 1.2:1:1.5, and the molar ratio of diamine-terminated polysiloxane and propylene oxide is 1:4.

[0060] The molar ratio of the double bonds on the pretreated polysiloxane in step B2 to DOPO is 1:1, the molar ratio of 3,4-dihydroxybenzoic acid to 4-formylphenylboronic acid is 1:1.3, and the amount of sodium carbonate used is 5% of the mass of 3,4-dihydroxybenzoic acid.

[0061] The molar ratio of the modifier and the modified polysiloxane described in step B3 is 2:1, the amount of p-toluenesulfonic acid monohydrate is 2% of the total mass of the modifier and the modified polysiloxane, the molar ratio of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol is 1:5:1:7.8, and the amount of antimony trioxide is 3% of the total mass of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol.

[0062] Example 3

[0063] A method for preparing a bio-based anti-drip PET fiber specifically comprises the following steps:

[0064] Calcium alginate fiber, modified polycaprolactone, glutaraldehyde and ethyl acetate are mixed and stirred for 4 hours at a speed of 80 r / min and a temperature of 50°C to obtain modified fibers. The following raw materials are weighed in parts by weight: 100 parts of modified PET and 20 parts of modified fibers. The raw materials are added into a twin-screw extruder and melt-extruded under the conditions that the temperatures in four zones are 230°C, 265°C, 265°C, and 265°C, respectively, and the pipeline temperature is 260°C. The raw materials are then melt-spun under the conditions that the number of spinneret holes is 36, the side blowing power is 10 Hz, the oil pump power is 20 Hz, the component pressure is 9 MPa, the spinning temperature is 280°C, and the winding speed is 800 m / min to obtain pretreated PET fibers. The pretreated PET fibers are immersed in an aqueous solution of zinc nitrate for 1-2 hours and dried to obtain bio-based anti-drip PET fibers.

[0065] The mass ratio of the calcium alginate fiber, modified polycaprolactone and glutaraldehyde is 1:10:0.05, and the mass fraction of the zinc nitrate aqueous solution is 10%.

[0066] The modified polycaprolactone is prepared by the following steps:

[0067] Step A1: 2,2-dihydroxymethylpropionic acid, acetyl chloride, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 150 r / min and a temperature of 0° C. for 15 h to obtain intermediate 1; intermediate 1, thionyl chloride and DMF were mixed, and the mixture was reacted at a speed of 200 r / min and a temperature of 90° C. for 12 h to obtain intermediate 2;

[0068] Step A2: The intermediate 2, 4-aminoimidazole, triethylamine and DMF were mixed evenly, and the mixture was reacted at a speed of 200 r / min and a temperature of -0°C for 5 h to obtain the intermediate 3. The intermediate 3 and deionized water were mixed evenly, and the mixture was stirred at a speed of 150 r / min and a temperature of 25°C, and sodium hydroxide was added to a pH value of 10, and the mixture was reacted for 3 h to obtain the modified monomer;

[0069] Step A3: The modified monomer, caprolactone, stannous octoate and toluene are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out at a speed of 80 r / min and a temperature of 120° C. for 25 hours to obtain modified polycaprolactone.

[0070] The molar ratio of 2,2-dihydroxymethylpropionic acid, acetyl chloride and triethylamine in step A1 is 1:2:2.1, and the molar ratio of intermediate 1 and thionyl chloride is 1:1.2.

[0071] The molar ratio of intermediate 2, 4-aminoimidazole and triethylamine described in step A2 is 1:1:1.2, and the amount ratio of intermediate 3 and deionized water is 1g:40mL.

[0072] The usage ratio of the modified monomer, caprolactone and stannous octoate described in step A3 is 60mmol:450mmol:2.5mL.

[0073] The modified PET is prepared by the following steps:

[0074] Step B1: Tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, propylene oxide and DMF are mixed uniformly, and the reaction is carried out for 8 hours at a speed of 200 r / min, a temperature of 50° C. and a pH value of 11 to obtain a pretreated polysiloxane;

[0075] Step B2: The pretreated polysiloxane, DOPO and DMF were mixed evenly, and reacted at a speed of 150 r / min and a temperature of 110° C. for 7 hours to obtain a modified polysiloxane; 3,4-dihydroxybenzoic acid, 4-formylphenylboric acid, sodium carbonate and chloroform were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 80 r / min and a temperature of 65° C. for 15 hours to obtain a modifier;

[0076] Step B3: The modifier, modified polysiloxane, p-toluenesulfonic acid monohydrate and isopropanol are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 18 hours at a speed of 200 r / min and a temperature of 25°C to obtain a flame retardant monomer. The flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite, ethylene glycol and antimony trioxide are mixed evenly, and the reaction is carried out for 5 hours at a temperature of 240°C and a pressure of 0.5 MPa. The temperature is raised to 285°C and the reaction is carried out for 30 minutes at a pressure of 80 Pa to obtain a modified PET.

[0077] The molar ratio of tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 1.2:1:1.5, and the molar ratio of diamine-terminated polysiloxane and propylene oxide is 1:4.

[0078] The molar ratio of the double bonds on the pretreated polysiloxane in step B2 to DOPO is 1:1, the molar ratio of 3,4-dihydroxybenzoic acid to 4-formylphenylboronic acid is 1:1.3, and the amount of sodium carbonate used is 5% of the mass of 3,4-dihydroxybenzoic acid.

[0079] The molar ratio of the modifier and the modified polysiloxane described in step B3 is 2:1, the amount of p-toluenesulfonic acid monohydrate is 2% of the total mass of the modifier and the modified polysiloxane, the molar ratio of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol is 1:5:1:7.8, and the amount of antimony trioxide is 3% of the total mass of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenyl hypophosphorous acid and ethylene glycol.

[0080] Comparative Example 1

[0081] Compared with Example 1, the comparative example was not immersed in the zinc nitrate aqueous solution, and the remaining steps were the same.

[0082] Comparative Example 2

[0083] Compared with Example 1, the modified polycaprolactone was not added in this comparative example, and the remaining steps were the same.

[0084] Comparative Example 3

[0085] Compared with Example 1, calcium alginate fiber was not added in this comparative example, and the remaining steps were the same.

[0086] Comparative Example 4

[0087] Compared with Example 1, this comparative example uses 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane instead of diamine-terminated polysiloxane, and the remaining steps are the same.

[0088] Comparative Example 5

[0089] Compared with Example 1, this comparative example uses p-formylbenzoic acid instead of the modifier, and the other steps are the same.

[0090] Comparative Example 6

[0091] Compared with Example 1, no flame retardant monomer was added in this comparative example, and the remaining steps were the same.

[0092] The bio-based anti-drip PET fibers obtained in Examples 1-3 and Comparative Examples 1-6 were made into 125mm×12mm×3mm samples according to the standard of GB / T2408-2008 to test the vertical burning level. They were made into 125mm×6mm×3mm samples according to the standard of GB / T2406.2-2009 to test the limiting oxygen index. They were made into short fibers with a mass of 0.4g according to the standard of GB / T20944.2-2007 to test the antibacterial effect. The test results are shown in the following table.

[0093]

[0094] It can be seen from the above table that the present invention has a good flame retardant and antibacterial effect.

[0095] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a bio-based anti-drip PET fiber, characterized in that: The specific steps include: Calcium alginate fiber, modified polycaprolactone, glutaraldehyde and ethyl acetate are mixed and stirred to obtain modified fiber, the following raw materials are weighed in parts by weight: 80-100 parts of modified PET and 10-20 parts of modified fiber, the raw materials are added into a twin-screw extruder, and melt-extruded under the condition that the four-zone temperature is 230° C., 265° C., 265° C., 265° C., and the pipeline temperature is 260° C., and then melt-spinned to obtain pretreated PET fiber, and the pretreated PET fiber is immersed in a zinc nitrate aqueous solution, immersed and dried to obtain bio-based anti-drip PET fiber; The mass ratio of the calcium alginate fiber, modified polycaprolactone and glutaraldehyde is 1:10:0.05, and the mass fraction of the zinc nitrate aqueous solution is 10%; The modified polycaprolactone is prepared by the following steps: Step A1: 2,2-dihydroxymethylpropionic acid, acetyl chloride, triethylamine and DMF are mixed, and the reaction is carried out for 10-15 hours at a speed of 120-150 r / min and a temperature of 0° C. to obtain intermediate 1; intermediate 1, thionyl chloride and DMF are mixed, and the reaction is carried out for 10-12 hours at a speed of 150-200 r / min and a temperature of 80-90° C. to obtain intermediate 2; Step A2: The intermediate 2, 4-aminoimidazole, triethylamine and DMF are mixed evenly, and the mixture is reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of -5-0°C to obtain the intermediate 3. The intermediate 3 and deionized water are mixed evenly, and the mixture is stirred at a speed of 120-150 r / min and a temperature of 20-25°C, and sodium hydroxide is added to the mixture until the pH value reaches 9-10, and the mixture is reacted for 2-3 hours to obtain the modified monomer. Step A3: uniformly mixing the modified monomer, caprolactone, stannous octoate and toluene, introducing nitrogen protection, and reacting for 20-25 hours at a speed of 60-80 r / min and a temperature of 110-120° C. to obtain modified polycaprolactone; The modified PET is prepared by the following steps: Step B1: Tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, tetramethylammonium hydroxide and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 90-95° C. to obtain a diamine-terminated polysiloxane; the diamine-terminated polysiloxane, propylene oxide and DMF are mixed uniformly, and the reaction is carried out for 6-8 hours at a speed of 150-200 r / min, a temperature of 40-50° C. and a pH value of 10-11 to obtain a pretreated polysiloxane; Step B2: The pretreated polysiloxane, DOPO and DMF are mixed evenly, and reacted at a speed of 120-150 r / min and a temperature of 100-110° C. for 5-7 hours to obtain a modified polysiloxane; 3,4-dihydroxybenzoic acid, 4-formylphenylboric acid, sodium carbonate and chloroform are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 60-80 r / min and a temperature of 60-65° C. for 10-15 hours to obtain a modifier; Step B3: The modifier, modified polysiloxane, p-toluenesulfonic acid monohydrate and isopropanol are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 15-18 hours at a speed of 150-200r / min and a temperature of 20-25°C to obtain a flame retardant monomer. The flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite, ethylene glycol and antimony trioxide are mixed evenly, and the reaction is carried out for 3-5 hours at a temperature of 230-240°C and a pressure of 0.3-0.5MPa. The temperature is raised to 280-285°C, and the reaction is carried out for 20-30 minutes at a pressure of 50-80Pa to obtain a modified PET.

2. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The molar ratio of 2,2-dihydroxymethylpropionic acid, acetyl chloride and triethylamine in step A1 is 1:2:2.1, and the molar ratio of intermediate 1 and thionyl chloride is 1:1.

2.

3. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The molar ratio of intermediate 2, 4-aminoimidazole and triethylamine described in step A2 is 1:1:1.2, and the amount ratio of intermediate 3 and deionized water is 1g:40mL.

4. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The modified monomer, caprolactone and stannous octoate used in step A3 are used in a ratio of 60 mmol:450 mmol:2.5 mL.

5. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The molar ratio of tetramethyltetravinylcyclotetrasiloxane, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and tetramethylammonium hydroxide in step B1 is 1.2:1:1.5, and the molar ratio of diamine-terminated polysiloxane and propylene oxide is 1:

4.

6. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The molar ratio of the double bonds on the pretreated polysiloxane in step B2 to DOPO is 1:1, and the molar ratio of 3,4-dihydroxybenzoic acid to 4-formylphenylboronic acid is 1:1.

3.

7. The method for preparing a bio-based anti-drip PET fiber according to claim 1, characterized in that: The molar ratio of the modifier and the modified polysiloxane in step B3 is 2:1, and the molar ratio of the flame retardant monomer, terephthalic acid, 2-carboxyethylphenylphosphite and ethylene glycol is 1:5:1:7.

8.

8. A bio-based anti-drip PET fiber, characterized in that: Prepared according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Melt direct spinning method for PLA (Polylactic Acid) fiber with metal modified cross esterification compound

    CN109594144A

  • Degradable PET packing belt with flame retardant effect

    CN113429755A